THE INTEGRATION OF ARTIFICIAL INTELLIGENCE IN LANGUAGE LEARNING TO PROMOTE CROSS-CULTURAL GLOBAL INTERACTION (Ustozlar uchun, 2026)
Artificial intelligence (AI) is rapidly transforming modern education, especially in the field of language learning. In recent years, AI-powered tools such as chatbots, speech recognition systems, translation applications, and intelligent tutoring platforms have become widely used to support learners in developing communication skills. These technologies provide interactive, flexible, and personalized learning environments that help students practice language in realistic contexts. This article explores how artificial intelligence contributes to improving language learning and promoting cross-cultural global interaction. The study focuses on the advantages, limitations, and educational impact of AI integration. The findings suggest that AI significantly enhances learners’ fluency, motivation, and intercultural communication skills when used effectively alongside traditional teaching methods.